Social adaptation towards unstable rubber price among smallholders - Saufe, Nur Aqilah (2018)
National Key Economic Area (NKEA) for rubber involves three (3) Entry Point Projects (EPPs) and one of the targets is to ensure sustainability of the upstream rubber industry in Malaysia. This EPP aims to increase the area of replanting and new planting of rubber by independent smallholders to 24,000 hectares. More replanting exercises can also be expected following the government’s rubber incentive to aid rubber smallholders suffering from weak commodity prices. Rubber smallholders produce 92.4% of the Malaysian rubber production. Nowadays, rubber smallholders need to face many challenges especially in rubber price fluctuation. The unstable prices of natural rubber could affect the income and socio-economics of the rubber smallholders. Thus, this research is focused on experienced of Malaysian smallholders with the aim to identify smallholders’ social adaptation level towards unstable rubber price. Studying these conditions is a basic necessity to identify areas, which need to be supported to increase productivity through appropriate planning and proper extension services. This study was conducted in four (4) districts area (Baling and Kulim, Kedah; Gua Musang and Kuala Krai, Kelantan) where most people are from rubber community and also the main occupation and income are from rubber with a total of 400 respondents. The primary data collected directly from the study of materials such as using questionnaire filled by the rubber smallholders as a respondent. The survey questions design according to the objectives of the study. Interviews for this surveys consisted of several structured questions such as demographic characteristic, respondents’ farm profile, impact of unstable rubber price, social adaptation toward the unstable rubber price, agricultural extension services and others. The data collected was analysed using descriptive analysis, chi-square analysis, factor analysis and multiple regression analysis. First, descriptive analysis was used to analyze the data which including the percentage and frequency. Chi-square analysis was used to test the association between selected socio-demographic factors and the level of respondents’ social adaptation towards unstable rubber price. Lastly, multiple regression analysis was applied to investigate the most influential factors of impact level of unstable rubber price towards social adaptation. The findings of descriptive analysis showed that 76.5% of respondents are male and the rest of 23.5% are female. The most predominant age group of the respondents is more 56 years old which are 42.0%. For the marital status of the respondents, there were 90.0% are married, 1.5% are single and 8.5% are widow and widower. 35.0% respondents went to primary schools while about 38.5% went to secondary schools. Meanwhile, only 4.0% had college/university education and 22.5% did not get any formal education. In general, the income level of smallholders is still low (68.5% less than RM1000). The main factors affecting the income of the smallholders are the current rubber price and the old age of the trees. The overall mean for social adaptation level of smallholders towards the impact of unstable rubber price is 3.65 considered as a moderate level of perception. The result showed that the impacts level of unstable rubber price of smallholders was very high. Moreover, the level of agricultural extension agencies’ roles to undertake impact of unstable rubber price toward respondents was very high. This study indicated that agricultural extension services have played a role in providing knowledge and information to improve smallholders’ social adaptation. The results of chi-square analysis showed that smallholders’ age, gender, marital status, years of involvement, number of household, age of rubber tree, yield per month and rubber price per kilogram had significant association with their level of respondents’ social adaptation towards unstable rubber price. Since the smallholders’ majority is more than 56 years old age, it shows the significant effect on social adaptation towards unstable rubber price. Meanwhile for education level, farm operation system, places that are yield delivered, gross income per month show no significant difference at all. Further, results of multiple regression analysis revealed that socio demographic factors (education level, years of involvement, yield and income) and impact factors (environment, socio economic, and psychology and emotion) were the most influential factors in respondents’ social adaptation towards unstable rubber price. In conclusion, this study impacts gave a clear picture and better insight in smallholders’ social adaptation towards unstable rubber price. The result showed the impact of unstable rubber price to smallholders was very high. Moreover, the level of social adaptation towards unstable rubber price was moderate. Assessing their levels of adaptation will assist the relevant agencies in understanding the readiness of the community to be transferred and to learn new knowledge and skills about rubber production and off-farm activities. An agricultural extension service has played a role in providing knowledge and information to improve smallholders’ yield and income to increase the level of smallholders’ social adaptation. Besides, extension services should give more intention to smallholders’ impact of unstable rubber price which are socio economy, environment and also psychology and emotion for increases of social adaptation level among smallholders. Thus, government subsidies should be continue to help farmers adapt with unstable rubber price. Government must be continuing support and should formulate new policies to increase social adaptation level among smallholders towards unstable rubber price.